Chemical composition and rheology of low-fat Iranian white cheese incorporated with guar gum and gum arabic as fat replacers - Lashkari, Hannan (Springer India, 2012)
The effects of incorporating guar gum (GG) and gum arabic (GA) in cheese-making milk with various fat contents (0.4, 0.9, and 1.4 %) on chemical and rheological properties of Iranian white cheese were evaluated by response surface method (RSM). As GG concentration increased, dry matter content of cheese samples decreased due to the high water binding capacity of this gum. A similar trend was also observed for GA at concentrations less than 150 ppm. The higher the GG concentration, the higher was the free fatty acid content of cheese samples. GA at concentrations more than 150 ppm, increased the storage modulus (G′), causing an undesirable hard texture for the product. The G′ and stress at fracture (б(f)) of samples decreased by the increasing concentration of GG incorporated into the cheese-making milk. Response surface minimization of rheological indices for Iranian white cheese showed that combination of two hydrocolloids (GG in the concentration range 75–170 ppm and GA at concentrations <75 ppm) would provide the softest texture.